Fostering Enterprise Performance Through Employee Brand Engagement and Knowledge Sharing Culture: Mediating Role of Innovative Capability - Zhang, Yaowen (Frontiers in Psychology, 2022)
Enterprise performance is a critical component of any organizational success that is directly affected by its employees and the culture prevailing in the organizations. In order to gain strategic advantage from the employee brand equity it is important that organizations make efforts in retaining such employees that benefit the organizations. Therefore, this research examines the impact of employee brand equity and knowledge sharing culture on the enterprise performance with the mediating role of innovative capabilities. A self-administered survey was conducted among the 323 employees of information technology sector working in the software houses in China. Smart PLS has been used to analyze the data through partial least square structural equation modeling. Results of the study have demonstrated that knowledge sharing culture plays a significant role in the enterprise performance while employee brand equity could not find statistically significant impact on enterprise performance. In addition, the SEM analysis further showed that employee brand equity and knowledge sharing culture play a significant role in the innovative capabilities. Results also revealed that innovative capabilities mediate the effect of employee brand equity and knowledge sharing culture variables on the enterprise performance. This research enriches the literature by examining the role of knowledge sharing culture in enterprise performance and innovative capabilities. This research further offers certain implications for the human resource department in developing their human resources. This can be achieved by availing the maximum skills of the branded employees by creating learning opportunities for the other employees through training sessions where they help and share their experiences.